The impact of COVID-19 on stock market returns in Vietnam - ao Van Hùng; Thi Minh Hue Nguyen; Thuy Duong Vu (Journal of Risk and Financial Management, 2021)
This paper studies the impacts of COVID-19 on the performance of the Vietnamese Stock Market-a rapidly growing emerging market in a country that has to date successfully controlled the disease outbreak. The study uses a random-effect model (REM) on panel data of stock returns of 733 listed companies on both HOSE (the Ho Chi Minh Stock Exchange) and HNX (the Hanoi Stock Exchange) from 2 January 2020 to 13 December 2020. The study shows that the number of daily COVID-19 confirmed cases in Vietnam has a negative impact on stock returns of listed companies in the market. The impacts were more severe for the pre-lockdown and second-wave period, compared to impact for the lockdown period. The impacts also differed across sectors, with the financial sector being the most affected. With significant government control and influence over the bank-dominated financial system, the financial sector was expected to absorb some of the negative shocks hitting the real sector. Such expectations were reflected in the stock market movement during the pandemic.
Keywords: 330; COVID-19; Vietnam; lockdown; pre-lockdown; second-wave; stock market; stock performance; stock return